Racial disparities in patients with coronavirus disease 2019 infection and gynecologic malignancy. Issue 7 (9th December 2020) - Lara, Olivia D.; Smith, Maria J.; Wang, Yuyan; O'Cearbhaill, Roisin; Blank, Stephanie V.; Kolev, Valentin; Carr, Caitlin; Knisely, Anne; McEachron, Jennifer; Gabor, Lisa; Chapman‐Davis, Eloise; Jee, Justin; et al.
Abstract : Background: Mounting evidence suggests disproportionate coronavirus disease 2019 (COVID‐19) hospitalizations and deaths because of racial disparities. The association of race in a cohort of gynecologic oncology patients with severe acute respiratory syndrome‐coronavirus 2 infection is unknown. Methods: Data were abstracted from gynecologic oncology patients with COVID‐19 infection among 8 New York City area hospital systems. A multivariable mixed‐effects logistic regression model accounting for county clustering was used to analyze COVID‐19–related hospitalization and mortality. Results: Of 193 patients who had gynecologic cancer and COVID‐19, 67 (34.7%) were Black, and 126 (65.3%) were non‐Black. Black patients were more likely to require hospitalization compared with non‐Black patients (71.6% [48 of 67] vs 46.0% [58 of 126]; P = .001). Of 34 (17.6%) patients who died from COVID‐19, 14 (41.2%) were Black. Among those who were hospitalized, compared with non‐Black patients, Black patients were more likely to: have ≥3 comorbidities (81.1% [30 of 37] vs 59.2% [29 of 49]; P = .05), to reside in Brooklyn (81.0% [17 of 21] vs 44.4% [12 of 27]; P = .02), to live with family (69.4% [25 of 36] vs 41.6% [37 of 89]; P = .009), and to have public insurance (79.6% [39 of 49] vs 53.4% [39 of 73]; P = .006). In multivariable analysis, among patients aged <65 years, Black patients were more likely to require hospitalization compared with non‐Black patients (odds ratio, 4.87; 95% CI, 1.82‐12.99; P = .002). Conclusions: Although Black patients represented only one‐third of patients with gynecologic cancer, they accounted for disproportionate rates of hospitalization (>45%) and death (>40%) because of COVID‐19 infection; younger Black patients had a nearly 5‐fold greater risk of hospitalization. Efforts to understand and improve these disparities in COVID‐19 outcomes among Black patients are critical. Abstract : Among women with gynecologic cancer who have coronavirus disease 2019 (COVID‐19) infection, Black patients are more likely to require hospitalization for COVID‐19 infection compared with non‐black patients. Younger Black patients aged <65 years have a nearly 5‐fold greater risk of hospitalization because of COVID‐19 infection.